Master regulator: p53’s pivotal role in steering NK-cell tumor patrol - Wang, Haohao; Chen, Qingjie; Liu, Qinghua; Luo, Changjiang (Frontiers in Immunology, 2024)
The p53 protein, encoded by TP53, is a tumor suppressor that plays a critical role in regulating apoptosis, cell cycle regulation, and angiogenesis in tumor cells via controlling various downstream signals. Natural killer (NK) cell-mediated immune surveillance is a vital self-defense mechanism against cancer and other diseases, with NK cell activity regulated by various mechanisms. Among these, p53 plays a significant role in immune regulation by maintaining the homeostasis and functionality of NK cells. It enhances the transcriptional activity of NK cell-activating ligands and downregulates inhibitory ligands to boost NK cell activation and tumor-killing efficacy. Additionally, p53 influences NK cell cytotoxicity by promoting apoptosis, autophagy, and ferroptosis in different tumor cells. p53 is involved in the regulation of NK cell activity and effector functions through multiple pathways. p53 also plays a pivotal role in the tumor microenvironment (TME), regulating the activity of NK cells. NK cells are critical components of the TME and are capable of directly killing tumor cells. And p53 mutates in numerous cancers, with the most common alteration being a missense mutation. These mutations are commonly associated with poor survival rates in patients with cancer. This review details p53's role in NK cell tumor immunosurveillance, summarizing how p53 enhances NK cell recognition and tumor destruction. We also explore the potential applications of p53 in tumor immunotherapy, discussing strategies for modulating p53 to enhance NK cell function and improve the efficacy of tumor immunotherapy, along with the associated challenges.Understanding the interaction between p53 and NK cells within the TME is crucial for advancing NK cell-based immunotherapy and developing p53-related novel therapeutics.